2021
DOI: 10.11591/ijai.v10.i4.pp810-817
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing digital marketing performance through usage intention of AI-powered websites

Abstract: <p><span>Digital and wireless technology are a crucial part of today’s modern life. Artificial intelligence (AI) uses different technologies and systems for speech recognition, visual perception and decision making to mimic human functions. This study explores the impact of AI on website interactivity and the ease of use for enhancing digital marketing performance. The methodology used is qualitative with structured interviews, using three artificial intelligence-powered websites (Amazon, Alibaba, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Market mavens are highly informed customers with a high level of marketing intelligence and marketing literacy. Intention to recommend is one of the ways to determine customer loyalty (Gong and Tung, 2017; Safi and Awan, 2018; Suleiman et al , 2021) and is an important attribute of market mavens. It acts as a free marketing tool and is essential in building consumers purchase decision (Khan et al , 2020; Ruiz-Mafe et al , 2020; Sharif et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Market mavens are highly informed customers with a high level of marketing intelligence and marketing literacy. Intention to recommend is one of the ways to determine customer loyalty (Gong and Tung, 2017; Safi and Awan, 2018; Suleiman et al , 2021) and is an important attribute of market mavens. It acts as a free marketing tool and is essential in building consumers purchase decision (Khan et al , 2020; Ruiz-Mafe et al , 2020; Sharif et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These authors examined how technical communication businesses reach the final consumer by using websites and search engines as intermediaries. Their results showed that this strategy was among the most helpful for directing people to companies' websites and, also, that the better the website, the better the feedback the company received (Killoran, 2009; Suleiman et al, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Indeed, the Artificial Intelligence (AI) platform is just that kind of technology forming the key enabler toward change with regard to practices within the digital marketing environments, for purposes like seeking more insight into customer behavior and preference (Mogaji et al, 2020). Having highlighted that fact, it is also a fact that AI will improve the performance of digital marketing for businesses but improve user engagements on their websites through secure and interactive systems (Suleiman et al, 2021). The use of digital marketing tools may also further enable the AI to tweak strategies by the companies to adapt to a change in consumer behavior by which improvement in the outcomes for marketing is realized (Zaman, 2022;Febriani et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As per Romero et al (2021) and Saqib and Zarine (2021), the usage of such tools is intended to let the company derive meaningful insights from customer data for better decision-making processes and efficient operations. Awareness of the implementation of AI features into digital marketing activities creates a platform toward more improved performance in business operations, as well as bringing deep insights into customer preferences (Suleiman et al, 2021;Aladayleh, 2020). BI tools also promote real-time analysis of customer feedback.…”
Section: H1: the Use Of Business Intelligence Tools Positively Influe...mentioning
confidence: 99%